Keharaman Transplantasi dan Donasi Organ: Perspektif Islam dan Kesehatan - Najla Malika; Nayla Nur Azikha Hakim; Salsabila Nur Hanifah (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
Organ transplantation is not a new medical procedure. It began with kidney transplantation, the first successful organ transplantation taking place in 1954, and has continued to evolve. To perform a transplantation, a source organ is needed for the procedure. Organs can be obtained from deceased donors, waiting for a donor from a waiting list, or seeking donors independently, which can include family, friends, or even unknown individuals through advertisements or social media. The primary reason for organ transplantation is the presence of organ abnormalities, usually affecting the kidneys or heart, which can significantly diminish a person's quality of life or even pose life-threatening risks. However, in Islam, there are prohibitions that make this essential procedure forbidden (haram). This article explores the Islamic perspective on organ donation practices and the reasons behind the prohibition of both donation and transplantation through a qualitative or library research method.